An Education and Training Program on Disaster Triage for Nurses and Nursing Students: Literature Review - Faizatiwahida, Novia; Setiyarini, Sri; Alim, Syahirul (Universitas Muhammadiyah Surakarta, 2024)
Natural disasters continue to increase globally yearly. Over 1.6 billion people live in disaster-prone areas, conflict zones, and displacement areas. The impacts of disasters highlight the importance of disaster preparedness to minimize errors in disaster triage management. However, nurses' knowledge and skills in implementing initial triage procedures are still adequate. This scooping review aims to find an overview of implementing disaster triage education and training programs. This research is a scooping review using the Prisma flow chart in its implementation. This study showed significant results in all articles (n = 14) in increasing knowledge, attitudes, skills, awareness, preparedness, accuracy, and learning motivation in conducting disaster triage. The methods used are simulation methods (live, virtual reality, and screen-based) and training and education methods (lectures, discussions, videos, roleplay, and games) with material on disaster triage, START triage, and SALT triage concepts. This study concluded that disaster triage education for nurses and nursing students is very important to be provided by carrying out the latest methods so that the results are more effective.